Pharmacologic Inhibition of ADAM10 Attenuates Brain Tissue Loss, Axonal Injury and Pro-inflammatory Gene Expression Following Traumatic Brain Injury in Mice - Appel, Dominik; Hummel, Regina; Weidemeier, Martin; Endres, Kristina; Gölz, Christina; Schäfer, Michael K. E. (Frontiers in Cell and Developmental Biology, 2021)
The α-secretase A disintegrin and metalloprotease 10 (ADAM10) regulates various physiological and pathophysiological processes. Despite its broad functional implications during development, plasticity, and disease, no pharmacological approaches to inhibit ADAM10 in acute brain injury have been reported. Here, we examined the effects of the ADAM10 inhibitor GI254023X on the neurological and histopathological outcome after experimental traumatic brain injury (TBI). C57BL/6N mice were subjected to the controlled cortical impact (CCI) model of TBI or sham procedure and received GI254023X or vehicle during the acute phase of injury (n=40, 100 mg/kg, 25 % DMSO, 0.1 M Na2CO3, intraperitoneal, 30 min and 24 h after TBI). GI254023X treatment did not improve neurological deficits from 1 to 7 days post-injury (dpi) but animals treated with GI254023X exhibited smaller brain lesions compared to vehicle treatment. Determination of brain mRNA expression by quantitative PCR showed that TBI-induced up-regulation of Adam10 and Adam17 was not influenced by GI254023X but the up-regulation of the matrix metalloproteinase genes Mmp2 and Mmp9 was attenuated. GI254023X treatment further increased the T cell marker Cd247 but did not affect blood brain barrier integrity, as assessed by Occludin mRNA expression and IgG brain extravasation. However, in agreement with neuroprotective effects of ADAM10 inhibition, GI254023X treatment attenuated axonal injury, as indicated by decreased generation of spectrin breakdown products (SBDPs) and decreased immunostaining using anti-non-phosphorylated neurofilament (SMI-32). Interestingly, reduced axonal injury in GI254023X-treated animals coincided with subtle mRNA dysregulation in the glutamate receptor subunit genes Gria1 and Grin2b. Quantitative PCR also revealed that GI254023X mitigated up-regulation of the pro-inflammatory markers Il6, Tnfa, and Lcn2 but not the up-regulation of the pan-microglia marker Aif1, the M2 microglia marker Arg1 and the reactive astrocyte marker Gfap. Taken together, the ADAM10 inhibitor GI254023X attenuates brain tissue loss, axonal injury and pro-inflammatory gene expression in the CCI model of TBI. These results suggest that ADAM10 may represent a therapeutic target in the acute phase of TBI.